Decrease of NAD+ Inhibits the Apoptosis of OLP T Cells via Inducing Mitochondrial Fission - Zhang ZY; Wang F; Zhou G (Journal of Inflammation Research)
Zhuo-Yu Zhang,1 Fang Wang,1,2 Gang Zhou1,3 1State Key Laboratory of Oral & Maxillofacial Reconstruction and Regeneration, Key Laboratory of Oral Biomedicine Ministry of Education, Hubei Key Laboratory of Stomatology, School & Hospital of Stomatology, Wuhan University, Wuhan, People’s Republic of China; 2Center for Cariology, Endodontics and Periodontics, Optical Valley Branch, School & Hospital of Stomatology, Wuhan University, Wuhan, People’s Republic of China; 3Department of Oral Medicine, School and Hospital of Stomatology, Wuhan University, Wuhan, People’s Republic of ChinaCorrespondence: Fang Wang, Center for Cariology, Endodontics and Periodontics, Optical Valley Branch, School & Hospital of Stomatology, Wuhan University, Wuhan, People’s Republic of China, Email wangfang-nm@whu.edu.cn Gang Zhou, Department of Oral Medicine, School and Hospital of Stomatology, Wuhan University, Wuhan, People’s Republic of China, Email zhougang@whu.edu.cnPurpose: Oral lichen planus (OLP) is a chronic, immune-mediated inflammatory disease involving T cells. Mitochondrial fission plays a crucial role in T cell fate through structural remodeling. Nicotinamide adenine dinucleotide (NAD+) regulates mitochondrial remodeling and function. This study explored the role of NAD+ in modulating mitochondrial fission and apoptosis in T cells under the OLP immune-inflammatory environment.Patients and Methods: T cells and plasma were isolated from peripheral blood. Mitochondrial morphology was characterized by transmission electron microscopy and Mito-Tracker staining. OLP plasma-exposed Jurkat T cells were infected with the Drp1 shRNA virus to investigate the role of mitochondrial fission in OLP T cell apoptosis. OLP T cells and OLP plasma-exposed Jurkat T cells were treated with either β-nicotinamide mononucleotide (an NAD+ synthesis precursor) or FK866 (an NAD+ synthesis inhibitor) to assess the effect of NAD+ regulation on mitochondrial remodeling and T cell apoptosis.Results: OLP T cells exhibited fragmented mitochondria with elevated dynamin-related protein 1 (Drp1) and reduced mitofusin 2 (Mfn2) expression, accompanied by decreased apoptosis. Drp1 knockdown in OLP plasma-exposed Jurkat T cells increased apoptosis and reduced proliferation. NAD+ levels were reduced in both OLP T cells and OLP plasma-treated Jurkat T cells, leading to enhanced mitochondrial fission, decreased mitochondrial membrane potential (MMP) and respiration function, and reduced apoptosis rate. β-nicotinamide mononucleotide supplementation restored NAD+ levels, suppressed mitochondrial fission, improved MMP, and promoted apoptosis in these cells.Conclusion: Reduced NAD+ levels in OLP T cells enhanced mitochondrial fission and contributed to decreased apoptosis. NAD+ supplementation mitigated these effects, suggesting a potential therapeutic strategy for restoring T cell homeostasis in OLP.Keywords: mitochondria, nicotinamide adenine dinucleotide, T cells, oral lichen planus